1996
DOI: 10.1007/bf02207275
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calmodulin expression prevents low-pH-induced gap junction uncoupling inXenopus oocytes

Abstract: The relationship among intracellular pH (pHi), -log10 intracellular Ca2+ concentration (pCai) and gap junctional conductance, the participation of Ca2+ stores, and the role of calmodulin in channel regulation have been studied in Xenopus oocytes, expressing the native connexin (Cx38), exposed to external solutions bubbled with 100% CO2. The time courses of pHi [measured with 2',7'-bis(2-carboxyethyl)-5,6-carboxyfluorscein (BCECF)], pCai (measured with the membrane-associated fura-C18) and junctional conductanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 34 publications
8
60
2
Order By: Relevance
“…This is in contrast to channels formed by connexins, which either are non-responsive to increased cytoplasmic calcium or are closed, depending on their protein composition [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to channels formed by connexins, which either are non-responsive to increased cytoplasmic calcium or are closed, depending on their protein composition [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that pH i can modulate gap junction permeability (Morley et al, 1996;Peracchia et al, 1996;Saez et al, 2005;Sosinsky and Nicholson, 2005), there is little available information about their role in synchronising pH i in connected cells. One recent study showed that microinjection of acid into cardiomyocytes causes detectable pH i decreases in adjacent cells (Zaniboni et al, 2003).…”
Section: Gap Junctions Permit Intercellular Ph Cooperativitymentioning
confidence: 99%
“…The molecular mechanisms that underlie this modulation of connexin channel activity are unclear and may differ among connexin isoforms and cell types. It has been proposed that the modulation is due to direct protonation of connexin (8), changes in ionized calcium concentration (11), and activation of calmodulin (12)(13)(14). For connexin-43 and for connexin-32/connexin-38 chimerae, recent work strongly indicates a pH-dependent interaction between segments of the C-terminal domain and the single cytoplasmic loop that inhibits channel activity (3,(15)(16)(17)(18)(19)(20)(21).…”
Section: Changes In Intracellular Ph (Ph I )mentioning
confidence: 99%